Narrow‐Band Screen‐Space Fluid Rendering. (9th April 2022) - Oliveira, Felipe; Paiva, Afonso
Abstract: This paper presents a novel and practical screen‐space liquid rendering for particle‐based fluids for real‐time applications. Our rendering pipeline performs particle filtering only in a narrow‐band around the boundary particles to provide a smooth liquid surface with volumetric rendering effects. We also introduce a novel boundary detection method allowing the user to select particle layers from the liquid interface. The proposed approach is simple, fast, memory‐efficient, easy to code and it can be adapted straightforwardly in the standard screen‐space rendering methods, even in GPU architectures. We show through a set of experiments how the prior screen‐space techniques can be benefited and improved by our approach. Abstract : This paper presents a novel and practical screen‐space liquid rendering for particle‐based fluids for real‐time applications.